Baculovirus as a Tool for Gene Delivery and Gene Therapy - Ono, Chikako; Okamoto, Toru; Abe, Takayuki; Matsuura, Yoshiharu (Viruses, 2018)
Based on its ability to express high levels of protein, baculovirus has been widely used for recombinant protein production in insect cells for more than thirty years with continued technical improvements. In addition, baculovirus has been successfully applied for foreign gene delivery into mammalian cells without any viral replication. However, several CpG motifs are present throughout baculoviral DNA and induce an antiviral response in mammalian cells, resulting in the production of pro-inflammatory cytokines and type I interferon through a Toll-like receptor (TLR)-dependent or -independent signaling pathway, and ultimately limiting the efficiency of transgene expression. On the other hand, by taking advantage of this strong adjuvant activity, recombinant baculoviruses encoding neutralization epitopes can elicit protective immunity in mice. Moreover, immunodeficient cells, such as hepatitis C virus (HCV)- or human immunodeficiency virus (HIV)-infected cells, are more susceptible to baculovirus infection than normal cells and are selectively eliminated by the apoptosis-inducible recombinant baculovirus. Here, we summarize the application of baculovirus as a gene expression vector and the mechanism of the host innate immune response induced by baculovirus in mammalian cells. We also discuss the future prospects of baculovirus vectors.